2010
DOI: 10.1002/jbmr.162
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the TNFRSF11A gene encoding RANK is associated with susceptibility to Paget's disease of bone

Abstract: RANK (receptor activator of nuclear factor-kB), encoded by TNFRSF11A, is a key protein in osteoclastogenesis. TNFRSF11A mutations cause Paget's disease of bone (PDB)-like diseases (ie, familial expansile osteolysis, expansile skeletal hyperphosphatasia, and early-onset PDB) and an osteoclast-poor form of osteopetrosis. However, no TNFRSF11A mutations have been found in classic PDB, neither in familial nor in isolated cases. To investigate the possible relationship between TNFRSF11A polymorphisms and sporadic P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 90 publications
4
37
1
Order By: Relevance
“…Two common polymorphisms have been described in the protein coding region of RANK [88] which are evolutionarily conserved [91]; these are a histidine to tyrosine amino acid change at codon 141 (H141Y) and an alanine to valine at codon 192 (A192V). Functional analyses of these polymorphisms have yielded mixed results; in one study no effect of these polymorphisms on RANK-induced NFkB activation was found in reporter assays [90], whereas in another study the alanine variant at codon 192 was reported to cause activation of RANK signaling in both the presence and the absence of the SQSTM1 P392L mutation [91]. Further studies will be required to confirm these observations and to determine if the A192V variant is fully responsible for the robust association that has been observed between PDB and common variants at the TNFRSF11A locus [4,49,90,93].…”
Section: Tnfrsf11amentioning
confidence: 95%
See 1 more Smart Citation
“…Two common polymorphisms have been described in the protein coding region of RANK [88] which are evolutionarily conserved [91]; these are a histidine to tyrosine amino acid change at codon 141 (H141Y) and an alanine to valine at codon 192 (A192V). Functional analyses of these polymorphisms have yielded mixed results; in one study no effect of these polymorphisms on RANK-induced NFkB activation was found in reporter assays [90], whereas in another study the alanine variant at codon 192 was reported to cause activation of RANK signaling in both the presence and the absence of the SQSTM1 P392L mutation [91]. Further studies will be required to confirm these observations and to determine if the A192V variant is fully responsible for the robust association that has been observed between PDB and common variants at the TNFRSF11A locus [4,49,90,93].…”
Section: Tnfrsf11amentioning
confidence: 95%
“…Mutations have not been detected in the exons or intronexon boundaries of TNFRSF11A in classical PDB [88,89], but there is evidence from candidate gene studies and genomewide association studies that common variants at the TNFRFS11A locus predispose to PDB [4,49,90]. Two common polymorphisms have been described in the protein coding region of RANK [88] which are evolutionarily conserved [91]; these are a histidine to tyrosine amino acid change at codon 141 (H141Y) and an alanine to valine at codon 192 (A192V).…”
Section: Tnfrsf11amentioning
confidence: 99%
“…The Belgian study population was described as previously (Chung et al 2010), but enlarged to 247 sporadic PDB patients, recruited from different clinical centres in Belgium. Diagnosis of PDB was based on alkaline phosphatase measurements and radiographic/scintigraphic examinations.…”
Section: Belgian Populationmentioning
confidence: 99%
“…DNA was extracted in a standard manner, using the salting out method (Miller et al 1988). No indication of population stratification was observed as described in our previous study (Chung et al 2010).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation